Masi: A mechanical ventilator based on a manual resuscitator with telemedicine capabilities for patients with ARDS during the COVID-19 crisis - Chang, Javier (2021)
This work has been funded by the 055-2020-FONDECYT GRANT from the Peruvian government and the donations of the enterprises mentioned in our webpage: https://www.proyectomasi.pe/.In addition,the authors would like to thank to all the members of the Masi team, especially to all of the collaborators working at the five institutions involved in this project (BREIN, DIACSA, EAT, PUCP and Zolid). Without all of their effort, professionalism and sacrifice while working steadily during the pandemic; this device would have not existed.